POSSIBILITIES FOR IMPROVING THE FUNCTIONS OF AUDIT COMMITTEE INMUNICIPALITIES - Gabov, Rumen (E-Journal VFU, 2025)
The relevance of the study is related to the continuous change in legal framework and the new emerging phenomena and processes requiring innovative thinking. The purpose of the research study is to identify opportunities for optimizе the function of the audit committee in municipalities, through the following tasks: showing conceptual framework; summarizing survey datas; presenting guidelines for improving the financial reporting process and the internal control system in municipal audit committee, for this purpose, the methods of scientific analysis an synthesis comparison and analysis of survey data (quantitative methods) are used. The process of monitoring financial reporting and the system of internal control by the municipal audit committee and giving guidelines for their improvement are two of the main functions of the committee, which, when united, would be lead to the generation of an additional synergistic effect of their implementation for the organization.
Keywords: financial report; audit committee; municipality; internal control systems